2023
DOI: 10.7150/thno.85250
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage promotes fibroblast activation and kidney fibrosis by assembling a vitronectin-enriched microenvironment

Abstract: Background : Renal infiltration of inflammatory cells including macrophages is a crucial event in kidney fibrogenesis. However, how macrophage regulates fibroblast activation in the fibrotic kidney remains elusive. In this study, we show that macrophages promoted fibroblast activation by assembling a vitronectin (Vtn)-enriched, extracellular microenvironment. Methods : We prepared decellularized kidney tissue scaffold (KTS) from normal and fibrotic kidney after unilateral isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…This further confirms that HIF-1α has the potential to regulate collagen expression to modulate the growth of PAECs and influence the development of ascites syndrome in broilers. It has been reported that cells promote fibrosis by assembling vitronectin-rich extracellular ecological niches ( Peng et al, 2023 ). The development of fibrosis is closely related to the development of BAS.…”
Section: Discussionmentioning
confidence: 99%
“…This further confirms that HIF-1α has the potential to regulate collagen expression to modulate the growth of PAECs and influence the development of ascites syndrome in broilers. It has been reported that cells promote fibrosis by assembling vitronectin-rich extracellular ecological niches ( Peng et al, 2023 ). The development of fibrosis is closely related to the development of BAS.…”
Section: Discussionmentioning
confidence: 99%
“… 168 A macrophage‐derived, Vtn‐enriched extracellular matrix scaffold was found to promote fibroblast activation and proliferation by stimulating integrin αvβ5 and Src kinase signalling. 169 Inhibition of (MMP‐9 produced by macrophages in late‐stage UUO reduced tubular cell EMT. Interestingly, MMP‐9 can also be expressed by myofibroblasts and further recruit macrophages.…”
Section: Fibroblast‐immunocyte Interactions and Organ Fibrosismentioning
confidence: 99%
“…We recently found that FBN1 exhibits significant upregulation in the decellularized kidney tissue scaffold (KTS) in CKD ( Li et al, 2021 ; Li et al, 2022 ; Li et al, 2023 ; Peng et al, 2023 ). Furthermore, FBN1 expression is elevated across many animal models of CKD as well as in individuals diagnosed with CKD.…”
Section: Fbn1 and Kidney Diseasesmentioning
confidence: 99%